Towards a normative theory of international relations : a critical analysis of the philosophical and methodological assumptions in the discipline with proposals towards a substantive normative theory - Frost, Mervyn Lowne (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1983.